A systematic evaluation of the firing temperatures of archaeological pottery from Catamarca, Argentina - Zagorodny, Nora Inés (2016)
Fil: Zagorodny, Nora Inés. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. Laboratorio de Análisis Cermámico (LAC); Argentina